Intertwined like a double helix: A meta‐synthesis of the qualitative literature examining the experiences of living with someone with multiple sclerosis. (4th February 2022) - Parkinson, Anne; Brunoro, Crystal; Leayr, Jack; Fanning, Vanessa; Chisholm, Katrina; Drew, Janet; Desborough, Jane; Phillips, Christine
Abstract: Background: Multiple sclerosis (MS) is a chronic serious condition of uncertain course and outcome. There is relatively little literature on the experiences of people who live with a person with MS. They inhabit a locus of care that spans caring for (a relational act) and caring about (a moral stance, addressing fairness, compassion and justice) the person with MS. Methods: Using the theoretical lens of personhood, we undertook a scoping review and meta‐synthesis of the qualitative literature on the experiences of people who live with a person with MS, focusing on the nature of, and constraints upon, caring. Results: Of 330 articles, 49 were included in the review. We identified five themes. One of these— seeking information and support —reflects the political economy of care. Two are concerned with the moral domain of care: caring as labour and living with uncertainty . The final two themes—c hanging identities and adapting to life with a person with MS —point to the negotiation and reconstitution of personhood for both the person with MS and the people they live with. Conclusion: People with MS are embedded in relational social networks of partners, family and friends, which are fundamental in the support of their personhood; the people who live with them are 'co‐constituents of the patient's identity' assisting them to make sense of their world and self in times of disruption due to illness. Support services and health care professionals caring for people with MS are currently very much patient‐centred; young people in particular report that their roles are elided in the health system's interaction with a parent with MS. There is a need to look beyond the person with MS and recognize the relational network of people who surround them and broaden their focus to encompass this network. Patient and Public Involvement: Our research team includes four members with MS and two members with lived experience of living or working with people with MS. A third person (not a team member) who lives with a partner with MS provided feedback on the paper.